2005
DOI: 10.1093/nar/gki641
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nuclear transport signals in the human apurinic/apyrimidinic endonuclease (APE1/Ref1)

Abstract: The mammalian abasic-endonuclease1/redox-factor1 (APE1/Ref1) is an essential protein whose subcellular distribution depends on the cellular physiological status. However, its nuclear localization signals have not been studied in detail. We examined nuclear translocation of APE1, by monitoring enhanced green fluorescent protein (EGFP) fused to APE1. APE1's nuclear localization was significantly decreased by deleting 20 amino acid residues from its N-terminus. Fusion of APE1's N-terminal 20 residues directed nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 51 publications
8
98
0
1
Order By: Relevance
“…Some evidence suggests that APE1/Ref-1 expression and subcellular localization are finely tuned. The subcellular distribution of APE1/Ref-1 may be regulated by both nuclear import and export systems (Jackson et al, 2005). APE1/Ref-1 undergoes active shuttling between the cytoplasm and nucleus in response to oxidative (Angkeow et al, 2002;Bhakat et al, 2003;Tell et al, 2000a) and nitrosative stress (Qu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence suggests that APE1/Ref-1 expression and subcellular localization are finely tuned. The subcellular distribution of APE1/Ref-1 may be regulated by both nuclear import and export systems (Jackson et al, 2005). APE1/Ref-1 undergoes active shuttling between the cytoplasm and nucleus in response to oxidative (Angkeow et al, 2002;Bhakat et al, 2003;Tell et al, 2000a) and nitrosative stress (Qu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the N-terminal region contains the redox regulatory domain characterized by 2 critical cysteine residues, C65 and C93 (Xanthoudakis et al, 1992;1994). Nuclear localization of APE1/Ref-1 is controlled by the first 20-35 amino acids at the N-terminal sequence (Jackson et al, 2005;Jeon et al, 2004). It also has been reported that nitrosation of APE1/Ref-1 leads to cytoplasmic localization in a chromosome region maintenance 1 (CRM1)-independent process (Qu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, we have also shown that the extract of mitochondria (containing processing peptidases) but not of nuclei or cytosol, cleaves recombinant hAPE1 to generate an mtAPE-sized product, implying that the removal of NLS is necessary for mitochondrial import of APE. At the same time, deletion mapping of hAPE1 helped us identify a bipartite NLS as well as a nuclear export signal in the N-terminal segment of the APE1 polypeptide [110].…”
Section: Ber In Mitochondriamentioning
confidence: 99%
“…This segment contains the nuclear localization signal (NLS) [110] and is also required for the transcriptional regulation function unique to APE1 and unrelated to BER [111,112]. We recently discovered that human APE1 (hAPE1) is acetylated in vivo at Lys 6 / Lys 7 which modulates its regulatory but not endonuclease activity [113].…”
Section: Mammalian Ape1 and E Coli Xth Have Distinct Propertiesmentioning
confidence: 99%
“…Three functionally independent domains can be distinguished within the APE1 protein ( Fig. 5): (i) the first 33-35 amino acid region consists of a structurally disordered segment (133) essential for the interaction with other proteins (148,149) and harboring sites for PTMs (14,24,70,89,159,165,166) and RNA interaction (89); (ii) the redox domain is located in a region between amino acids 35 and 127; and (iii) the DNA repair domain, which spans the C-terminal domain of the protein from about residue 61 onwards (42,68). Whereas the APE1 C-terminal domain involved in AP endonuclease activity is conserved from bacteria to humans, the N-terminal region is unique to mammals suggesting a recent acquisition during evolution.…”
Section: Fig 5 Schematic Representationmentioning
confidence: 99%